(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article presents a comparative semantic analysis of somatic phraseological units in the English and Uzbek languages. Somatic idioms, involving body parts (e.g., head, heart, hand), reflect the cognitive and cultural worldview of a speech community. Through analysis of selected examples, this study highlights similarities and differences in the conceptualization and figurative usage of somatic expressions across both languages. The findings illustrate how culture, emotion, and cognition intersect in idiomatic expressions and suggest implications for translation and language learning. The article presents theoretical ideas in this regard and proves them with examples.